Results of the Italian cross-sectional web-based survey “Nutrition and breast cancer, what would you like to know?” An attempt to collect and respond to patients’ information needs, through social media - Caprara, Greta; Pagan, Eleonora; Titta, Lucilla; Tieri, Maria; Magionesi, Giada; Gallosti, Silvia; Bagnardi, Vincenzo; Mazzocco, Ketti; Mazza, Manuelita (Frontiers in Oncology, 2024)
IntroductionSeveral studies have demonstrated that, following a breast cancer (BC) diagnosis, patients are eager to obtain information on cancer and nutrition, in order to ameliorate both their quality of life (QoL) and disease outcome. To avoid BC survivors to get wrong information from unreliable sources, healthcare providers need to be aware of patients’ needs, to guide them toward optimal nutrition recommendations, aimed at preventing tumor recurrence and increasing survival rates.Material and methodsThe cross-sectional web-based survey “Nutrition and breast cancer, what would you like to know?” has been conceived and conducted, in Italy, between the 2nd and the 25th of June 2023. The link to the 19-items questionnaire, structured in 6 sections, was distributed via social media (Facebook and Instagram), newsletter, institutional websites, and printed flyers. Patients’ responses were collected and analyzed, reporting absolute and relative frequencies.ResultsA total of 1616 participants (98.9% female and 1.1% male), with an average age of 47.5 years, answered the survey. Only subjects who declared having previously received a BC diagnosis (N=1159, 71.7%) were included in the present analysis. Overall, the respondents showed a wide interest in understanding whether nutrition might help to manage therapy side effects, as well as knowing how specific diets, foods, nutrients, and supplements could affect disease onset, progression and prognosis. Importantly, the need to receive evidence-based information from the “referring physician/specialist” and “nutritionist/dietitian” was expressed by 95.8% and 88.8% of them, respectively.DiscussionIn this study, we primarily aimed at intercepting nutrition information needs and sources of an Italian BC survivors’ group. Based on that, we first organized a proactive digital intervention, to respond via Instagram live broadcasts to patients’ “cancer and nutrition”-related questions. Secondly, we arranged a healthcare providers dedicated-workshop focused on the latest evidence-based knowledge on nutrition and BC. It is crucial, in fact, that once healthcare professionals capture patients’ information needs, they can respond with appropriate nutritional guidance, counseling and education programs, while counteracting misleading and incorrect messages.